Role of Individual Heat Transfer Mechanisms Within a Model Baking Oven Heated by Porous Volumetric Ceramic Burners - Jovicic, Vojislav; Zbogar-Rasic, Ana; Burjakow, Benedikt; Delgado, Antonio (Frontiers in Chemistry, 2020)
The baking process demands a high amount of energy, but only one-third of the total energy supply to the baking oven is actually used for baking, while the rest is dissipated to the environment. This implies that the energy input to the baking process can be significantly reduced, e.g., by enabling a more efficient heat transfer to the product, compared to commercially available ovens. Application of highly radiative, gas-fired heat sources, with a wide power modulation range, such as porous volumetric ceramic burners (VCB), can lead to a reduction in both the baking time and the energy input to a baking oven. In order to optimize energy input to a wide variety of baking products, the role of individual mechanisms in heat transfer between a heat source and a baking product needs to be determined. In the scope of this work, the analysis of the heat transfer within a baking oven model, heated by porous VCBs, was conducted. Contribution of heat transfer mechanisms (heat conduction, convection, thermal radiation) to the total heat transfer was determined by the difference method, where two aluminum cubes of different surface characteristics were used as target objects. Further, the influence of water, commonly added to the baking chamber in form of steam or aerosol, on the heat transfer characteristics within the oven was investigated. Without water addition, the heat transfer between the porous VCBs and the test object occurred mainly through thermal radiation (~45%), followed by heat conduction and convection (~27.5% each). Compared to the reference, commercially available electrical deck baking oven, the share of thermal radiation in the model oven was increased (+ 10%), whereas the share of heat conduction was reduced (−20%). With water addition, the heat transfer to the test object through heat conduction, convection, and thermal radiation declined, as an additional heat transfer through condensation took place. Results of this research provide necessary understanding of the heat transfer mechanisms within the novel baking oven, heated by porous VCBs. They are the base for optimization of the heat transfer from the VCBs to different baking goods, through changing the VCB's operating parameters.